Reduction of Salmonella Shedding by Sows during Gestation in Relation to Its Fecal Microbiome - Larivière-Gauthier, Guillaume; Thibodeau, Alexandre; Letellier, Ann; Yergeau, Étienne; Fravalo, Philippe (Frontiers in Microbiology, 2017)
Pork meat is estimated to be responsible for 10 to 20% of human salmonellosis cases in Europe. Control strategies at the farm could reduce contamination at the slaughterhouse. One of the targeted sectors of production is maternity, where sows could be Salmonella reservoirs. The aim of this study was to assess the dynamics of shedding of Salmonella in terms of variation in both shedding prevalence and strains excreted during gestation in Quebec’s maternity sector. The evolution of the fecal microbiota of these sows during gestation was also assessed in order to detect bacterial populations possibly associated with these variations. A total of 76 sows both at the beginning and the end of the gestation were randomly selected and their fecal matter was analysed. Salmonella detection was conducted using a method that includes two selective enrichment media (MSRV and TBG). Nine isolates per positive samples were collected. Among the 76 sows tested, 31 were shedding Salmonella. Sows in the first third of their gestation shed Salmonella significantly more frequently (21/27) than those in the last third (5/46) (χ² P < 0.05). The shedding status of 19 of the sows that were previously sampled in the first third of their gestation was followed, this time in the last third of their gestation, which confirmed reduction of shedding. Using 16S rRNA gene sequencing and qPCR, significant differences between the fecal flora of sows at the beginning and the end of the gestation and shedding Salmonella or not was detected. Using LefSe, multiple bacterial phyla were found to be associated with the time of gestation and the status of excretion. Some of the identified taxa such as the genus Barnesiella could be linked to the reduction of the shedding of Salmonella at the end of gestation. In this study, we showed that the level of Salmonella shedding was variable during gestation with significantly higher shedding at the beginning rather than at the end of gestation. We also observed for the first time a significant change in the microbiota during sow gestation and identified interesting taxa which could be linked to a reduced Salmonella shedding.